New imperatives of human security - Haq, Mabub ul (UNDP New YorkUS, 1994)
Suggests five steps that can lead towards a new Human World Order viz to seek a new concept of development; to move from arms security to human security; to create a new partnership between North and South; to fashion a new framework of global governance; and, to assist in the evolution of a global civil society.